Energy Drink Consumption in Europe: A Review of the Risks, Adverse Health Effects, and Policy Options to Respond - Breda, João Joaquim; Whiting, Stephen Hugh; Encarnação, Ricardo; Norberg, Stina; Jones, Rebecca; Reinap, Marge; Jewell, Jo (Frontiers in Public Health, 2014)
With the worldwide consumption of energy drinks increasing in recent years, concerns have been raised both in the scientific community and among the general public about the health effects of these products. Recent studies provide data on consumption patterns in Europe; however, more research is needed to determine the potential for adverse health effects related to the increasing consumption of energy drinks, particularly among young people. A review of the literature was conducted to identify published articles that examined the health risks, consequences, and policies related to energy drink consumption. The health risks associated with energy drink consumption are primarily related to their caffeine content, but more research is needed that evaluates the long-term effects of consuming common energy drink ingredients. The evidence indicating adverse health effects due to the consumption of energy drinks with alcohol is growing. The risks of heavy consumption of energy drinks among young people have largely gone unaddressed and are poised to become a significant public health problem in the future.